Human Need for Religion: Imam Al-Ghazali's Perspective - Ani Nuraeni, Heni; Mutiara Gahana, Nibras; Rihadatul Aisy, Nabila (Peneliti.net, 2023)
The Concept of Fulfilling Life's Needs According to al Ghazali. This research was motivated by the author's anxiety about Islamic graduates in researching Islamic studies. The author sees a kind of loss of identity in Islamic scholarship due to the lack of studies and searches for previous Islamic scholarship. Western concepts are widely used to solve problems that arise in society, so the author chose this comparative study. The focus of the study is related to the issue of the necessities of life which are very crucial for human survival, so this comparative research aims to reveal the concept of fulfilling the necessities of life according to al Ghazali. The main approach used in this research is descriptive qualitative. This study cannot be separated from human and religious values, so the author also uses a phenomenological approach to acknowledge the existence of ethical and transcendental truths and accept certain subjectivities as truth, and cannot be separated from the psychological approach. The results of the research can be found that al Ghazali's concept of the necessities of life in his language starts from Hifz al Din, Hifz al Nafs, Hifz al Mal, Hifz al Aql to Hifz al Nasb, so that the concept looks spiritualistic-materialistic.